PROVISION OF LEGAL AID TO CHILDREN AS VICTIMS OF SEXUAL VIOLENCE IN THE FAMILY ENVIRONMENT (STUDY AT POSBAKU AISYIYAH NORTH SUMATERA) - Daulay, Riska Romaito (Inspiring Law Journal, 2025)
Legal aid is a constitutional right of every citizen to guarantee legal protection and guarantee equality before the law, as a means of recognizing human rights that are non-derogable rights, namely a right that cannot be reduced and cannot be suspended under any circumstances. The provision of legal aid is not a mercy given by the state, but rather a basic human right of every individual and is the responsibility of the state to protect the poor. An important means of guaranteeing the basic human rights of citizens and realizing equality before the law, as regulated in Article 27 paragraph (1) of the 1945 Constitution and Law Number 16 of 2011 concerning Legal Aid. Posbakum Aisyiyah North Sumatra is present as a legal aid institution that provides assistance, consultation, and legal advocacy, especially for women and children who are victims of violence. Through cooperation with institutions such as LPSK and the Women and Children Empowerment Service, Posbakum Aisyiyah North Sumatra plays an active role in protecting and restoring victims legally and psychologically. The implementation of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS) is an important foundation in protecting victims of sexual violence, especially in the household sphere. Legal aid is not only a form of social responsibility of advocates, but also part of the justice system that guarantees justice and protection of human rights for all citizens, without exception.